Absolute reliability and concurrent validity of the modified goniometric platform for measuring trunk rotation in the sitting position - Gao, Jianhong; Thung, Jin Seng; Wei, Shanshan; Pavlu, Dagmar; Chee, Chen Soon; Ramasamy, Yuvaraj; Mohd Ali, Azril Syazwan; Mat Yatim, Rosnah (Multidisciplinary Digital Publishing Institute, 2022)
The modified goniometric platform (MGP) is a novel instrument used to measure trunk rotation while sitting. A lack of reliable and valid evidence has been reported to measure trunk rotation using MGP. Therefore, this study was aimed to investigate the intra- and inter-rater reliabilities and validity of the MGP for measuring trunk rotation while sitting. Methods: Seventeen participants performed right trunk rotation followed by left trunk rotation (three repetitions for each trial) and two random measurements at 40-minute intervals. Inter-rater and intra-rater reliabilities were calculated using intraclass correlation coefficients (ICCs). Validity was assessed using the Pearson correlation coefficient (r). Results: The test and re-test inter-rater reliabilities for right trunk rotation were 0.990 and 0.986, respectively, and those for left trunk rotation were 0.989 and 0.978, respectively. The intra-rater reliabilities for right trunk rotation were 0.949 and 0.954, respectively, and those for left trunk rotation were 0.944 and 0.946, respectively. The right and left trunk rotation validities were 0.986 and 0.981, respectively. Conclusion: MGP is reliable and valid for measuring right and left trunk rotations while sitting.